Metabolic and Behavior Changes in Surubim Acutely Exposed to a Glyphosate-Based Herbicide - Sinhorin, Valeria D. G.; Sinhorin, Adilson P.; Teixeira, Jhonnes Marcos S.; Mileski, Kelly Marcia L.; Hansen, Paula Carine; Moeller, Paulo Rafael; Moreira, Paula Sueli A.; Baviera, Amanda Martins [UNESP]; Loro, Vania L. (Springer, 2014)
This study examined the effect of glyphosate-based herbicide (Roundup Original), the major herbicide used in soybean crops in Mato Grosso state, at concentrations of 0, 2.25, 4.5, 7.5, and 15 mg L-1 on metabolic and behavior parameters of the hybrid fish surubim in an acute exposure lasting 96 h. Glycogen content, glucose, lactate, and protein levels were measured in different tissues. Plasma levels of cholesterol, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were also determined. Ventilatory frequency (VF) and swimming activity (SA) were considered behavior parameters. Results showed that herbicide exposure decreased plasma glucose levels and increased it in surubim liver. Lactate increased in both plasma and liver but decreased in muscle. Protein levels decreased in plasma and muscle but increased in liver. After herbicide exposure, liver and muscle glycogen was decreased. Cholesterol levels decreased in plasma at all concentrations tested. Plasma ALT increased, and no alterations were recorded for AST levels. VF increased after glyphosate exposure (5 min) and decreased after 96 h. SA showed differences among all groups (5 min). At the end of 96 h, SA was altered by the 7.5 mg L-1 concentration. Fish used anaerobic glycolysis as indicated by generally decreased glycogen levels and decreased lactate levels in muscle but increased ones in plasma and liver. We suggest that the studied parameters could be used as indicators of herbicide toxicity in surubim and may provide extremely important information for understanding the biology of the animal and its responsiveness to external stimuli (stressors).